Early events in tissues during infection with pathogenic (SIVmac239) and nonpathogenic (SIVmac1A11) molecular clones of simian immunodeficiency virus. - Lackner, A. A. (1994)
The extent of virus replication, tissue distribution, localization of virus within tissues, and the presence of pathological lesions was examined early after experimental infection of rhesus monkeys with simian immunodeficiency virus (SIV). Three strains of SIV were used: molecularly cloned pathogenic SIVmac239; molecularly cloned nonpathogenic SIVmac1A11; and uncloned pathogenic SIVmac. The major targets of infection in all animals at 2 weeks postinoculation were the thymus and spleen. The distribution of virus within lymphoid organs varied with the viral inoculum: nonpathogenic SIVmac1A11 was present primarily within lymphoid follicles and in the thymic cortex; SIVmac239 was present primarily within periarteriolar lymphoid sheaths in the spleen, the paracortex of lymph nodes, and the medulla of the thymus; uncloned SIVmac was present in all these areas but tended to parallel the distribution of SIVmac239. Animals inoculated with nonpathogenic SIVmac1A11 had fewer SIV-positive cells by in situ hybridization and after 13 weeks postinoculation, virus was undetectable in any tissue from these animals. No significant pathological abnormalities were recognized in animals inoculated with this nonpathogenic virus. In contrast, nearly half of the animals inoculated with either SIVmac or SIVmac239 developed significant pathological lesions, including opportunistic infections by 13 weeks postinoculation, highlighting the virulence of these viruses. Our results indicate marked differences in tissue distribution between pathogenic and nonpathogenic molecular clones of SIV during the acute phase of infection. The most striking differences were the absence of SIVmac1A11 from the central nervous system and thymic medulla. The prominent early involvement of the thymus suggests that infection of this organ is a key event in the induction of immune suppression by SIV.